Learning foreign languages in companies that provide in-house vocational training : exemplary strategies - Schröder, Ulrike [Verfasser] (My University, 2007)
"The importance of "Europeanizing" vocational training - and concomitantly the need to teach foreign languages on an occupation-related basis - has grown significantly in recent years. The work programme that was formulated on the basis of the Lisbon strategy and approved by the EU education ministers and the European Commission back in 2002 cites the promotion of foreign language learning as one of the 13 key objectives that European education policy is to implement by the year 2010." (BIBB)
Erstveröffentlichung der englischen Version des Artikels in: BWP Special Edition 2005, S. 15-17
Keywords: L 1.6.2 Fremdsprachen; S 1.3.1 Ausbildung im Dualen System; Spracherwerb; Sprachkenntnisse; Betriebliche Berufsausbildung